2011
DOI: 10.1161/circep.110.961243
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Inappropriate or “Unnecessary” Implantable Cardioverter-Defibrillator Shocks

Abstract: L ife-saving shocks are the raisons d'être of implantable cardioverter-defibrillators (ICDs). Paradoxically, shocks also cause much of the morbidity associated with ICDs. Consistently, shocks reduce quality of life, 1,2 and rarely, they may cause proarrhythmia. 3,4 Additionally, shocks have been reported to be associated with excess mortality. 5 Experts disagree about whether shocks are responsible for this excess mortality, 6 but they do agree that ICDs should deliver the fewest shocks necessary to protect pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 77 publications
(83 reference statements)
1
35
0
1
Order By: Relevance
“…We summarize the most commonly used discriminators. More comprehensive discussions are available in the literature [107][108][109][110][111].…”
Section: Svt-vt Discriminator Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We summarize the most commonly used discriminators. More comprehensive discussions are available in the literature [107][108][109][110][111].…”
Section: Svt-vt Discriminator Componentsmentioning
confidence: 99%
“…Approaches to minimizing Twave oversensing include reprogramming ventricular sensitivity, altering sensing bandwidth, and changing the sensing bipole [109,123,145]. One manufacturer provides an algorithm that withholds therapy after rate and duration criteria for VT/VF are fulfilled if a specific pattern of T-wave oversensing is identified [146].…”
Section: Programming To Reduce T-wave Oversensingmentioning
confidence: 99%
“…35) Optimal ICD programming to minimize inappropriate ICD shock such as higher detection rates, prolonged detection intervals, and supraventricular tachycardia discriminators is critically important. 36) Considering the high incidence of inappropriate shock and high ventricular rate during VF episodes, a more conservative approach in detection of VF (from 200 bpm to 240 bpm or higher) is required. 37) Anti-arrhythmic drugs are considered the first-line therapy to prevent the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Although therapy delivered for a ventricular tachyarrhythmia is considered appropriate, a growing body of evidence has shown that programming antitachycardia pacing (ATP) or delaying shocks to permit nonsustained episodes to terminate significantly reduces the frequency of shock delivery. Koneru et al 14 have used the term unnecessary shocks to refer to inappropriate shocks delivered for rhythms other than VT/VF and to include shocks delivered for VT that would have responded to ATP or terminated spontaneously if given time. Optimal programming minimizes unnecessary shocks.…”
Section: Inappropriate Shocks and Unnecessary Shocksmentioning
confidence: 99%
“…In the only currently available s-ICD, rate is programmable but not duration. The 25% to 75% time from detection to shock is 13 to 16 seconds, 14 so that the use of a detection rate of 200 bpm results in a therapy delay slightly longer than that in the delayed-therapy arm of MADIT-RIT. Recommended programming parameters for the primary prevention indication at our institution are presented in the Table.…”
Section: Icd Shock-reduction Strategies: Overviewmentioning
confidence: 99%